Transformational Leadership , Emotional Intelligence , and Perceived Organizational Support (POS) on Organizational Citizenship Behavior (OCB) of employees at the Nias Regency DPRD office - Olida Jaya Zai; Rini Sarianti (Human Resource Management Studies, 2022)
This study aims to analyze: (1) The Effect of Transformational Leadership on Organizational Citizenship Behavior (OCB) of employees at the Nias Regency DPRD office (2) The Effect of Emotional Intelligence on Organizational Citizenship Behavior (OCB) of employees at the Nias Regency DPRD office (3) The Effect of Perceived Organizational Support for the Organizational Citizenship Behavior (OCB) of employees at the Nias Regency DPRD office. The sampling technique in this study was a cluster proportional random sampling technique, with a total sample of 67 people. The results show that: (1) Transformational Leadership has a positive and significant effect on Organizational Citizenship Behavior (OCB) of employees at the Nias Regency DPRD office, (2) Emotional Intelligence has a positive and significant effect on the Organizational Citizenship Behavior (OCB) of employees at the Nias Regency DPRD office, (3) Perceived Organizational Support has a positive and significant impact on the Organizational Citizenship Behavior (OCB) of employees at the Nias Regency DPRD office